The intergenerational transmission of employers - Miles Corak; Patrizio Piraino (Institute for the Study of Labor (IZA), 2010)
We find that about 40% of a cohort of young Canadian men has been employed with an employer for whom their father also worked; and six to nine percent have the same employer in adulthood. The intergenerational transmission of employers is positively related to paternal earnings, particularly at the very top of the earnings distribution, and to the presence of self-employment income and the number of employers with which the father has had direct contact. It has an important influence in determining nonlinear patterns in the intergenerational elasticity of earnings.
Keywords: J62; J64; 330; Intergenerational mobility; job search; Arbeitsplatz; Arbeitsuche; Intergenerational Mobility; Familiensoziologie; Soziale Beziehungen; Kanada